3, 4‐Dihydroxybenzaldehyde lowers ROS generation and protects human red blood cells from arsenic(III) induced oxidative damage. Issue 8 (6th May 2018) - Maheshwari, Nikhil; Khan, Fahim Halim; Mahmood, Riaz
Abstract: Arsenic (As) is a potent environmental toxicant and chronic exposure to it results in various malignancies in humans. Oxidative stress has been implicated in the etiopathogenesis of As‐induced toxicity. This investigated the protective effect of plant antioxidant 3, 4‐dihydroxybenzaldehyde (DHB) on sodium meta‐arsenite (SA), an As‐(III) compound, induced oxidative damage in human red blood cells (RBC). The RBC were first incubated with different concentrations of DHB and then treated with SA at 37°C. Hemolysates were prepared and assayed for various biochemical parameters. Treatment of RBC with SA alone enhanced the generation of reactive oxygen species and increased lipid and protein oxidation. Reduced glutathione levels, total sulfhydryl content and cellular antioxidant power were significantly decreased in SA alone treated RBC, compared to the untreated control cells. This was accompanied by membrane damage, alterations in activities of antioxidant enzymes and deranged glucose metabolism. Incubation of RBC with DHB, prior to treatment with SA, significantly and dose‐dependently attenuated the SA‐induced changes in all these parameters. Scanning electron microscopy of RBC confirmed these biochemical results. Treatment of RBC with SA alone converted the biconcave discoids to echinocytes but the presence of DHB inhibited this conversion and the RBC retained their normal shape. These results show that DHB protects human RBC from SA‐induced oxidative damage, most probably due to its antioxidant character.